Experimental Induction of a Perceived “Telescoped” Limb Using a Full-Body Illusion - Schmalzl, Laura; Ehrsson, H H. (Frontiers in Human Neuroscience, 2011)
Phantom limbs refer to the sensation that an amputated or missing limb is still attached to the body. Phantom limbs may be perceived as continuous with the stump so as to resemble a normal limb, or as “telescoped” with the more distal portion of the phantom being perceived as having withdrawn within the stump. Telescoping tends to be related to increased levels of phantom pain, making it a clinically relevant phenomenon to investigate. In the current study we show that a full-body illusion can be used to induce the sensation of a telescoped limb in healthy individuals. For the induction of the full-body illusion, participants saw the body of a mannequin from a first person perspective while being subjected to synchronized visuo-tactile stimulation through stroking. Crucially, the mannequin was missing its left hand so as to resemble an amputee. By manipulating the positioning of the strokes applied to the mannequin’s stump with respect to the participants’ hand we were able to evoke the sensation of the participants’ hand being located either below the stump or, more crucially, “inside” the stump, i.e. telescoped. In three separate experiments these effects were supported by complementary subjective data from questionnaires, verbally reported perceived location of the hand, and manual pointing movements indicating hand position (proprioceptive drift). Taken together our results show that healthy individuals can experience the body of an upper limb amputee as their own, and that this can be associated with telescoping sensations. This is a theoretically important observation as it shows that ownership of an entire body can be evoked in the context of gross anatomical incongruence for a single limb, and that telescoping sensations occur as a consequence of the body representation system trying to reduce this incongruence. Furthermore, the present study might provide a new platform for future studies of the relationship between telescoping and phantom pain in amputees.